2008
DOI: 10.1007/978-3-540-74805-2_10
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Receptors for Dopamine, Histamine, and Serotonin

Abstract: Presynaptic receptors for dopamine, histamine and serotonin that are located on dopaminergic, histaminergic and sertonergic axon terminals, respectively, function as autoreceptors. Presynaptic receptors also occur as heteroreceptors on other axon terminals. Auto- and heteroreceptors mainly affect Ca(2+) -dependent exocytosis from the receptor-bearing nerve ending. Some additionally subserve other presynaptic functions.Presynaptic dopamine, histamine and serotonin receptors are involved in various (patho)physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 260 publications
1
33
0
1
Order By: Relevance
“…Changes in extracellular [GABA] may result from changes in the amount of released GABA or its uptake. Presynaptic effects of DA on neuronal GABA release are well-established (Feuerstein 2008;Zhang and Sulzer 2012), and we did observe decreases in frequency of mIPSCs after DA (30 nM) or quinpirole application, without concomitant changes in postsynaptic mIPSC kinetic parameters. These data suggested that the observed DA actions on I tonic might be mediated by changes in synaptic GABA release.…”
Section: Discussionsupporting
confidence: 54%
“…Changes in extracellular [GABA] may result from changes in the amount of released GABA or its uptake. Presynaptic effects of DA on neuronal GABA release are well-established (Feuerstein 2008;Zhang and Sulzer 2012), and we did observe decreases in frequency of mIPSCs after DA (30 nM) or quinpirole application, without concomitant changes in postsynaptic mIPSC kinetic parameters. These data suggested that the observed DA actions on I tonic might be mediated by changes in synaptic GABA release.…”
Section: Discussionsupporting
confidence: 54%
“…Neurotransmitter release is regulated locally by feedback inhibition through autoreceptors (adrenergic receptors that inhibit further NE release), and feedback inhibition of NE release can occur as a result of other chemicals, including 5-HT. Feuerstein (2008) published a comprehensive review of presynaptic receptors for dopamine, histamine, and 5-HT. Although autoinhibition of serotonergic nerves through 5-HT receptors makes intuitive sense, the finding of 5-HT receptors on adrenergic nerves is less intuitive.…”
Section: F 5-hydroxytryptamine Influence On the Autonomic Control Ofmentioning
confidence: 99%
“…Although autoreceptor-mediated regulatory mechanisms for classical neurotransmitters, such as dopamine and serotonin, are known to contribute to a local feedback mechanism in neural circuits (Feuerstein, 2008), evidence for autoreceptors in peptidergic system is still limited (Hökfelt et al, 2000). The presence of both BNP and NPR-A in peptidergic small DRG neurons and the effect of BNP on the firing rate of small DRG neurons suggest that NPR-A serves as an autoreceptor on some nociceptive afferent neurons.…”
Section: Presynaptic Mechanism For Bnp-induced Inhibitionmentioning
confidence: 99%